2022
DOI: 10.3390/jpm12020207
|View full text |Cite
|
Sign up to set email alerts
|

CRIDECO Anticholinergic Load Scale: An Updated Anticholinergic Burden Scale. Comparison with the ACB Scale in Spanish Individuals with Subjective Memory Complaints

Abstract: The increase in life expectancy has also been accompanied by an increase in the use of medication to treat chronic diseases. Polypharmacy is associated with medication-related problems such as the increase in the anticholinergic burden. Older people are more susceptible to anticholinergic effects on the central nervous system and this, in turn, may be related to cognitive impairment. In this paper, we develop an updated anticholinergic burden scale, the CRIDECO Anticholinergic Load Scale (CALS) via a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 68 publications
0
44
0
Order By: Relevance
“…We then adjusted the 21 models for the peripheral subscore and the 22 for the central subscore with the same set of previously selected covariates. Fourteen scales were significantly associated with the peripheral subscore in multiple logistic regression models when using the "max" method, the "sum" method, or both (Standardized β: 0.032 ≤ β ≤ 0.157; 0.09 ≤ R 2 ≤ 0.10) (Supplementary Table 4): the Anticholinergic Burden Classification (Ancelin et al, 2006), the Anticholinergic Risk Scale (Rudolph et al, 2008), the Anticholinergic Cognitive Burden scale (Boustani et al, 2008), the Anticholinergic Impregnation Scale (Briet et al, 2017), the Brazilian Anticholinergic Activity Drug Scale (Nery & Reis, 2019), the CRIDECO Anticholinergic Load Scale (Ramos et al, 2022), the Delirogenic Risk Scale (Hefner et al, 2015), Durán's scale (Durán et al, 2013), the German Anticholinergic Burden Scale (Kiesel et al, 2018), the Korean Anticholinergic 14 Burden Scale (Jun et al, 2019), the Muscarinic Acetylcholinergic Receptor ANTagonist Exposure Scale (Klamer et al, 2017), the modified Anticholinergic Cognitive Burden Scale of Joshi et al (2021), the modified Anticholinergic Risk Scale of Sumukadas et al (2016), and Salahudeen's scale (Salahudeen et al, 2015).…”
Section: Self-reported Side Effects and Anticholinergic Burden Scalesmentioning
confidence: 99%
“…We then adjusted the 21 models for the peripheral subscore and the 22 for the central subscore with the same set of previously selected covariates. Fourteen scales were significantly associated with the peripheral subscore in multiple logistic regression models when using the "max" method, the "sum" method, or both (Standardized β: 0.032 ≤ β ≤ 0.157; 0.09 ≤ R 2 ≤ 0.10) (Supplementary Table 4): the Anticholinergic Burden Classification (Ancelin et al, 2006), the Anticholinergic Risk Scale (Rudolph et al, 2008), the Anticholinergic Cognitive Burden scale (Boustani et al, 2008), the Anticholinergic Impregnation Scale (Briet et al, 2017), the Brazilian Anticholinergic Activity Drug Scale (Nery & Reis, 2019), the CRIDECO Anticholinergic Load Scale (Ramos et al, 2022), the Delirogenic Risk Scale (Hefner et al, 2015), Durán's scale (Durán et al, 2013), the German Anticholinergic Burden Scale (Kiesel et al, 2018), the Korean Anticholinergic 14 Burden Scale (Jun et al, 2019), the Muscarinic Acetylcholinergic Receptor ANTagonist Exposure Scale (Klamer et al, 2017), the modified Anticholinergic Cognitive Burden Scale of Joshi et al (2021), the modified Anticholinergic Risk Scale of Sumukadas et al (2016), and Salahudeen's scale (Salahudeen et al, 2015).…”
Section: Self-reported Side Effects and Anticholinergic Burden Scalesmentioning
confidence: 99%
“…We used two scales to allow for a more rigorous and robust characterization of AC medications in the sample and to evaluate commonalities in findings across coding schemes. The ACB Scale has been widely used in studies of aging (see, inter alia, Abbreviations: AC, anticholinergic; ACB Scale, Anticholinergic Cognitive Burden Scale (Boustani et al, 2008;Campbell et al, 2013); AD8, Eight-item Interview to Differentiate Aging and Dementia (Galvin et al, 2005(Galvin et al, , 2007; CALS, CRIDECO Anticholinergic Load Scale (Ramos et al, 2022); PRMQ, Prospective and Retrospective Memory Questionnaire.…”
Section: Coding Of Medicationsmentioning
confidence: 99%
“…The CALS characterizes AC potency on a scale from 1 to 3, where 1 corresponds to "low potency" and 3 to "high potency." In developing the CALS, Ramos et al (2022) sought to provide an up-to-date, comprehensive scale of ACB. Using a systematic literature review following the PRISMA guidelines, the authors identified seven AC scales used in Ecuador, Germany, Korea, New Zealand, and the United States of America.…”
Section: Coding Of Medicationsmentioning
confidence: 99%
See 2 more Smart Citations